2020
DOI: 10.1007/s00464-020-07950-5
|View full text |Cite
|
Sign up to set email alerts
|

Length of Barrett’s esophagus in the presence of low-grade dysplasia, high-grade dysplasia, and adenocarcinoma

Abstract: Introduction The identification and follow-up of ultra-short Barrett's esophagus (BE) is controversial. BE surveillance guidelines emphasize mainly on long-segment BE. However, in practice a substantial proportion of esophageal adenocarcinoma (EAC) are found close to the gastro-esophageal junction (GEJ). Our study aims to chart the length of BE when low-grade dysplasia (LGD), high-grade dysplasia (HGD) and EAC arise in BE. Methods Endoscopic findings from all cases with a diagnosis of LGD and HGD in BE between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In cases where multiple biopsies from different sites were available, the biopsy from the most distal aspect of BE segment was selected for analysis. This selection was based on data that suggests that a substantial proportion of dysplasia and EAC occurs in the distal oesophagus, close to the gastro-oesophageal junction 13 14. In 41/75 cases, we examined a single NDBE biopsy, in 28/75 cases we evaluated two serial NDBE biopsies and in 6/75 cases we examined 3 serial NDBE biopsies obtained at different time intervals (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In cases where multiple biopsies from different sites were available, the biopsy from the most distal aspect of BE segment was selected for analysis. This selection was based on data that suggests that a substantial proportion of dysplasia and EAC occurs in the distal oesophagus, close to the gastro-oesophageal junction 13 14. In 41/75 cases, we examined a single NDBE biopsy, in 28/75 cases we evaluated two serial NDBE biopsies and in 6/75 cases we examined 3 serial NDBE biopsies obtained at different time intervals (figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…recently reported that almost 20% of all dysplasia in BE and EAC occurs within a centimeter of the EGJ, suggesting that all lengths of CLE above the EGJ should be recognized as BE and subjected to a thorough biopsy protocol. 50 …”
Section: Diagnosis Of Bementioning
confidence: 99%
“…48 Although most studies show that the incidence of EAC in BE of less than 1 cm in length is very low, 49 Barrie et al recently reported that almost 20% of all dysplasia in BE and EAC occurs within a centimeter of the EGJ, suggesting that all lengths of CLE above the EGJ should be recognized as BE and subjected to a thorough biopsy protocol. 50 Traditionally, BE is divided into long-segment BE (LSBE, ≥3 cm) and SSBE (<3 cm) based on the length of columnar mucosa in the distal esophagus as assessed by endoscopy. Although not clearly defined in all guidelines, BE less than 1 cm in length is termed ultrashort-segment BE (USSBE).…”
Section: What Is the Optimal Landmark For The Egj?mentioning
confidence: 99%
See 1 more Smart Citation
“…By extension, it may be difficult to accurately report on the presence or absence of irregular Z-line, which is 1 cm or less in extent. The concern around irregular Z line comes from studies that have shown that as much as 20% of all dysplasia occurs in BE <1 cm and 20% of EAC occur within one cm of gastroesophageal junction [23]. These authors recommended that all lengths of columnar lined epithelium above the gastroesophageal junction be recognized as Barrett's metaplasia and be surveyed.…”
Section: Irregular Z Line and Risk Of Progressionmentioning
confidence: 99%